2010
DOI: 10.1111/j.1745-4603.2010.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and Instrumental Techniques Evaluating the Effect of Structure Parameters on the Tactile Properties of Knitted Fabrics

Abstract: In the present study, the effects of structure and process parameters on the tactile properties of cotton‐knitted fabrics had been investigated. The examined parameters were elastane plating, count of yarns and English gauge of knitting machine. The tactile quality was measured using sensory analysis and instrumental techniques. The obtained results showed that the variations of the production parameters induce a significant effect on 11 sensory attributes assessed by a French‐trained panel. Compression and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Smooth feel showed a strong negative correlation with surface roughness R a when a 10× objective lens was used (correlation coefficient = −0.769). Previous studies have suggested that a smooth feel is perceived when the variation of the frictional force with respect to the average frictional force is small [3335]. Figure 9 shows the relationship between smooth feel, surface roughness and friction variation value.…”
Section: Resultsmentioning
confidence: 97%
“…Smooth feel showed a strong negative correlation with surface roughness R a when a 10× objective lens was used (correlation coefficient = −0.769). Previous studies have suggested that a smooth feel is perceived when the variation of the frictional force with respect to the average frictional force is small [3335]. Figure 9 shows the relationship between smooth feel, surface roughness and friction variation value.…”
Section: Resultsmentioning
confidence: 97%
“…Sensory analysis has been reported to detect significant differences, as determined by yarn count, yarn torsion and fabric tightness. 38 Jeguirim et al 22 pointed out that the more the yarn is coarse, the more the fabric is thick, heavy, rigid and less soft. Among fabrics obtained from Tuscan wools, Panama, Diagonale-8 and Diagonale-5 had a statistically significant lower grittiness as compared to Drap-3 and Lisca pesce-10.…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…37 PCA has been already applied in studies on textiles. 22,25,39 This statistical technique offers a simple and reliable way to examine the correlations between variables. Furthermore, PCA allows a reduction in the dimension number of the representation.…”
Section: Sensory Evaluationmentioning
confidence: 99%
See 2 more Smart Citations